THEORETICAL AND PRACTICAL ASPECTS OF THE INVESTMENT RESOURCES ACCUMULATION - Kostyshyna, M. T.; Sushchenko, O. S. (Science and Transport Progress, 2008)
Theoretical and practical problems of accumulating investment resources as well as the investment as one of the aspects of planning the state economic policy have been considered in the article.